Assessing psychometric properties of the strength-based parenting questionnaire in Chinese adolescents - Lan Wen; Yaqing Huang; Yang Liu; Shuyue Zhang (Acta Psychologica)
This study aimed to validate and assess the psychometric properties of the Chinese adaptation of the Strength-Based Parenting Questionnaire (SBPQ) for the first time. A sample of 1590 middle school students participated in this investigation. Both exploratory factor analysis and confirmatory factor analysis revealed that a 13-item two-factor structure (Strength-Based Parenting Knowledge, SBP-K, and Strength-Based Parenting Use, SBP-U) fit the data well (χ2/df = 8.138, RMSEA = 0.076, CFI = 0.962, TLI = 0.953, SRMR = 0.037), consistent with the original two-factor model. Moreover, internal consistency and test-retest reliability for the total scale and two subscales were found to be within the adequate range. Furthermore, the scores of the SBPQ, SBPQ-K, and SBPQ-U showed significant positive correlations with strengths knowledge scale (SKS), strengths use scale (SUS), and parental autonomy support/parental emotional warmth subscale in s-EMBU-C (Short-Egna Minnenav Barndoms Uppfostran-Chinese), while displaying significant negative correlations with parental protection subscale. The results of the cross-group measurement invariance models revealed that the SBPQ met configural invariance, metric invariance, scalar invariance, and residual invariance in participants of different genders, family structures, and family locations. Notably, scores among males were significantly higher than those of females, and two-parent children had higher scores than single-parent and other children. The scores of urban, township, and rural children decreased successively, with rural students scoring significantly lower than their counterparts did. In conclusion, the modified Chinese version of the Strength-based Parenting Questionnaire (SBPQ) appears to be a valid and reliable measure that is appropriate for widespread use among Chinese adolescent populations.